2022
DOI: 10.55705/cmbr.2022.351720.1051
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS Analysis of the Active Compound in Ethanol Extracts of White Pepper (Piper nigrum L.) and Pharmacological Effects

Abstract: Pepper (Piper nigrum L.) has been utilized since antiquity and is considered the king of spices due to its wide use. This study aims to analyze the active compounds of white pepper through GC-MS and their pharmacological effects. Pepper seeds were extracted using 96% ethanol as solvent by the maceration method. The active compounds in the dry extract were then analyzed by GC-MS. Identification of the active compound was carried out by matching it to the Willey7 Library database. Based on the results chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
1
0
1
Order By: Relevance
“…Recently, several studies have focused on the effect of different plant extracts on the function of different human body systems and healthy complexion (29)(30)(31)(32). Momordica charantia fruit contains flavonoid components that can regulate cholesterol and lipoproteins levels (33).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have focused on the effect of different plant extracts on the function of different human body systems and healthy complexion (29)(30)(31)(32). Momordica charantia fruit contains flavonoid components that can regulate cholesterol and lipoproteins levels (33).…”
Section: Discussionmentioning
confidence: 99%
“…The work of Ojo et al ( 2021) showed a great antibacterial power of purified piperine on S. aureus and E. coli and S. enterica. However, the work done by Arsana et al (2022) showed that white P. nigrum would also contain Piperine. This difference observed in the antimicrobial activity could be explained by the difference in the composition of the different P. nigrum tested.…”
Section: Discussionmentioning
confidence: 99%
“…Plant phytochemicals are the first line of treatment for all types of human cancers in traditional medicine. Some studies have shown that medicinal plants and their isolated compounds suppress the expression of certain genes and specific biosynthetic pathways involved in cancer development (35)(36)(37). Anticancer activity of ethanol extracts of roots and aerial parts of nine ethnopharmacological medicinal plants of Golestan province (Iran), in terms of their cytotoxicity against L-929, AGS, HT-29, and esophageal adenocarcinoma cells, through promoting apoptosis and immunomodulatory effects.…”
Section: Discussionmentioning
confidence: 99%